Effect of CPP‐ACP modified‐GIC on prevention of demineralization in comparison to other fluoride‐containing restorative materials. (11th March 2022) - Sobh, EG; Hamama, HH; Palamara, JEA; Mahmoud, SH; Burrow, MF
Abstract: Background: This study evaluated the ability of a CPP‐ACP‐modified Glass–ionomer cement (GIC) to inhibit demineralization around the margins of cervical cavities in natural teeth in comparison with a Giomer and conventional GIC with and without coating. Methods: Thirty‐two sound human molars were used. Box‐shaped cavities were prepared along the CEJ. Teeth were randomly divided into four groups and restored with Equia Forte Fil, Coated Equia Forte Fil, Fuji VII EP or Beautifil II. Teeth were subjected to pH cycling. Micromorphological and elemental analyses were done using SEM and EDX. Polarized light microscope analysis and microhardness tests were also performed. Results: Microhardness tests on enamel showed a significant difference between the coated Equia group, Equia and Beautifil II groups ( P < 0.05). Dentine results showed significant differences between the coated Equia group and all other groups ( P < 0.05). Elemental analysis showed significant differences in calcium weight percentage among the first and second observation levels in all groups ( P < 0.05). A significant difference was found between the coated Equia group and the other three groups ( P < 0.05). Conclusions: All tested materials showed some ability to resist demineralization at the restoration margins. The coated GIC restoration showed better outcomes compared with the other tested materials.